BANGKITAN LALU LINTAS PADA PERUMAHAN BULAN TERANG UTAMA JALAN KI AGENG GRIBIG KOTA MALANG - Mite, Adrianus Raimundus; Pandulu, Galih Damar; Arifianto, Andi Kristafi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Each residential area development will have an impact on the environment and surrounding areas, one of which impact traffic. Housing Bulan Terang Utama, a housing unit located in the suburbs, the number of 3,000 units, on a land area of 200 hectares, the housing for the people of middle-prioritized, is also among the middle and above. This housing development should pay attention to road conditions and where the access to housing, so that the capacity of the existing road network will be exceeded, as the number of traffic generation and attraction due to the existence of such housing. Each residential area development will have an impact on the environment and surrounding areas, one of which impact traffic. Housing Bulan Terang Utama, a housing unit located in the suburbs, the number of 3,000 units, on a land area of 200 hectares, the housing for the people of middle-prioritized, is also among the middle and above. This housing development should pay attention to road conditions and where the access to housing, so that the capacity of the existing road network will be exceeded, as the number of traffic generation and attraction due to the existence of such housing. This study attempts to assess a housing development Bulan Terang Utama affecting traffic congestion, so as to know how big the impact on roads Ki Ageng Gribig. Currently the traffic impacts that occur as a result of the housing Bulan Terang Utama Key by using comparative data is not affecting the performance of the road itself. The magnitude of the maximum trip generation that occurs is 8.2%, with an average speed of vehicles on the road each Ki Ageng Gribik is 30.449 km / h, the degree of saturation is 1.27 with a traffic volume of 3661.67 SMP / h, the level of service Ki Ageng Gribik road included in the E-class level of service, speed of flow is unstable sometimes stalled, demand is approaching capacity of the road (ie 2089.044). Keywords: Housing, Traffic Impact, Road Service Levels. ABSTRAK Setiap pengembangan kawasan permukiman akan menimbulkan dampak bagi lingkungan dan sekitarnya, salah satunya dampak lalu lintas. Perumahan Bulan Terang Utama, merupakan unit perumahan yang berada pada kawasan pinggir kota, dengan jumlah 3.000 unit, pada lahan seluas 200 hektar, perumahan tersebut diprioritaskan bagi rakyat menengah kebawah, juga kalangan menegah ke atas. Pengembangan perumahan ini harus memperhatikan kondisi dan keberadaan jalan akses ke lokasi perumahan, sehingga kapasitas jaringan jalan yang ada akan terlampaui, seiring dengan pertambahan bangkitan dan tarikan lalu lintas akibat keberadaan perumahan tersebut. Akses jalan dari dan menuju lokasi perumahan Bulan Terang Utama dihubungkan oleh jalan Ki Ageng Gribig, yang merupakan jalan utama, sebagai akses lalu lintas masyarakat sekitar Kecamatan Kedungkandang, dari dan ke tengah kota, sehingga pembangunan kawasan perumahan tersebut membutuhkan akses transportasi yang memadai. Penelitian ini mencoba untuk mengkaji suatu pembangunan perumahan Bulan Terang Utama yang berdampak terhadap kemacetan lalu lintas, sehingga dapat diketahui seberapa besar dampak terhadap ruas jalan Ki Ageng Gribig. Saat ini dampak lalu lintas yang terjadi akibat adanya perumahan Bulan Terang Utama dengan menggunakan data pembanding adalah tidak mempengaruhi dari kinerja jalan itu sendiri. Besarnya bangkitan perjalanan maksimal yang terjadi adalah 8,2 %, dengan kecepatan rata-rata tiap kendaraan pada jalan Ki Ageng Gribik adalah 30,449 km/jam, derajat kejenuhannya adalah 1,27 dengan volume lalu lintas sebesar 3661,67 SMP/jam, tingkat pelayanan jalan Ki Ageng Gribik termasuk dalam tingkat pelayanan jalan kelas E, Arus tidak stabil kecepatan terkadang terhenti, permintaan sudah mendekati kapasitas jalan (yaitu 2089,044). Kata Kunci: Perumahan, Dampak Lalu Lintas, Tingkat Pelayanan Jalan.